Measurement of the pseudorapidity and transverse momentum dependence of the elliptic flow of charged particles in lead-lead collisions at $\sqrt{s_{NN}}=2.76$ TeV with the ATLAS detector - ATLAS collaboration (3031 authors) (2013)
This paper describes the measurement of elliptic flow of charged particles in lead-lead collisions at sqrt(s_NN) = 2.76 TeV using the ATLAS detector at the Large Hadron Collider (LHC). The results are based on an integrated luminosity of approximately 7 ub^-1. Elliptic flow is measured over a wide region in pseudorapidity, |eta| < 2.5, and over a broad range in transverse momentum, 0.5 < p_T < 20 GeV. The elliptic flow parameter v_2 is obtained by correlating individual tracks with the event plane measured using energy deposited in the forward calorimeters. As a function of transverse momentum, v_2(p_T) reaches a maximum at p_T of about 3 GeV, then decreases and becomes weakly dependent on p_T above 7 - 8 GeV. Over the measured pseudorapidity region, v_2 is found to be approximately independent of |eta| for all collision centralities and particle transverse momenta, something not observed in lower energy collisions. The results are discussed in the context of previous measurements at lower collision energies, as well as recent results from the LHC.